COVID-19, science, vaccines and family in a multi origin Latinx population in South Florida - Bastida, Elena; Ravelo, Gira J.; Benitez, Pablo; Chavez, Jennifer; Metheny, Nicholas; Baeza Robba, María José; Colón-Burgos, José Félix; De La Rosa, Mario; Behar-Zusman, Victoria; Carrasquillo, Olveen (Frontiers in Public Health, 2022)
During the Spring of 2021 in Miami-Dade County, four virtual focus groups were held with 31 participants from four diverse local Latinx communities as part of the Florida Community Engagement Alliance (FL-CEAL) Against COVID-19 Disparities project. The main objective was to explore attitudes about COVID-19 information and prevention strategies among South Florida's diverse Latinx populations, across a broad geographical area. The study used a semi-structured focus group qualitative design and chose participants from four well established Latinx neighborhoods. Participants were mostly women, diversity was strong with birth regions including the Caribbean, North, Central and South America. Though a third (n = 11) were born in the United States, almost all (n = 28) reported speaking Spanish at home. Three themes and six subthemes were identified to underscore Latinx attitudes toward COVID-19 vaccine uptake or hesitancy. These were: (1) Attitudes regarding vaccine intake; (2) Sources of Information; and (3) Science Education. The degree to which each of these themes exercised influence on vaccine intake or hesitancy varied. The multi origin Latinx participation in the focus groups strengthened findings by broadening representation and discussion. In the end and despite the various national origins, all participants indicated receiving most of their information on COVID-19 related topics from their family, physicians, social networks, and some form of media.